2002
DOI: 10.1007/bf02976599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of diacylglycerol acyltransferase by tanshinones from the root ofSalvia miltiorrhiza

Abstract: The inhibitory activity of tanshinones from Salvia miltiorrhiza was tested on rat liver diacylglycerol acyltransferase (DGAT). Cryptotanshinone (1) and 15,16-dihydrotanshinone I (3) exhibited potent DGAT inhibitory activities dose-dependently with IC50 values of 10.5 microg/ml and 11.1 microg/ml. However, tanshinone IIA (2) and tanshinone I (4) showed very weak inhibition (IC50 value: > 250 microg/ml). A dihydrofuran moiety was seemed to be responsible for the stronger inhibitory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…151). Numerous agents have been reported to inhibit DGAT activity, including a variety of substances isolated from microorganisms (152)(153)(154)(155)(156) and fish oils (157), but it is unclear whether these agents inhibit one or both DGAT enzymes. Recently, a selective smallmolecule inhibitor of DGAT1 was reported to reduce weight gain and hepatic TG when administered to mice fed a high-fat diet (115).…”
Section: Dgat Inhibitorsmentioning
confidence: 99%
“…151). Numerous agents have been reported to inhibit DGAT activity, including a variety of substances isolated from microorganisms (152)(153)(154)(155)(156) and fish oils (157), but it is unclear whether these agents inhibit one or both DGAT enzymes. Recently, a selective smallmolecule inhibitor of DGAT1 was reported to reduce weight gain and hepatic TG when administered to mice fed a high-fat diet (115).…”
Section: Dgat Inhibitorsmentioning
confidence: 99%
“…Although there are no available synthetic inhibitors of DGAT1, several naturally occurring compounds have been reported to inhibit DGAT activity in vitro. [23][24][25][26][27][28] To date, no studies to our knowledge have reported the effects of these DGAT inhibitors on energy and glucose metabolism in animal models. It is also unclear whether these compounds specifically inhibit DGAT1 or also antagonize the activities of DGAT2.…”
Section: From Mice To Humans: Clinical and Pharmaceutical Implicationsmentioning
confidence: 99%
“…The flavonoids inhibited DGAT activity in a dose-dependent manner with IC 50 values of 10.9 mM (1), 9.8 mM (2), 8.6 mM (3), 142.0 mM (4) and 250 mM (5). The prenylflavonoids without C3-OH (1,2,3) showed stronger inhibition than those with C3-OH (4,5). On the other hand, flavonoids without side chains (hesperetin, naringenin, quercetin and kaempferol) did not inhibit the enzyme activity at a final concentration of 800 mM.…”
Section: Introductionmentioning
confidence: 91%
“…Four prenylflavonoids, kurarinone (1), a chalcone of 1, kuraridin (2), kurarinol (3), kushenol H (4) and kushenol K (5) isolated from the roots of Sophora flavescens were investigated for their inhibitory effects on diacylglycerol acyltransferase (DGAT). The flavonoids inhibited DGAT activity in a dose-dependent manner with IC 50 values of 10.9 mM (1), 9.8 mM (2), 8.6 mM (3), 142.0 mM (4) and 250 mM (5).…”
Section: Introductionmentioning
confidence: 99%